2001
DOI: 10.1530/eje.0.1440509
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, leptin, IGF-I and insulin-dependent protein concentrations after insulin-sensitizing therapy in obese women with polycystic ovary syndrome

Abstract: Objective: To determine the clinical, hormonal and biochemical effect of 4±5 months of insulinsensitizing therapy (hypocaloric diet metformin) in obese patients with polycystic ovary syndrome (PCOS). Design: Prospective study. Methods: Twenty-three obese patients with PCOS, 19 obese patients without menstrual disturbances and 11 healthy control women were recruited from the Department of Endocrinology and Endocrine Gynecology, Medical Academy, Biaøystok, Poland. Obese patients received 500 mg metformin togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
6
34
0
3
Order By: Relevance
“…In general, patients present lower levels of IGF binding protein-I, leading to increased ovarian bioavailability of IGF-I. On the basis of these observations, clinical trials have been conducted to assess whether metformin affects IGF pathways or its binding proteins (20)(21)(22)(23). Unfortunately, this issue remains controversial.…”
Section: Related Biomarkersmentioning
confidence: 99%
“…In general, patients present lower levels of IGF binding protein-I, leading to increased ovarian bioavailability of IGF-I. On the basis of these observations, clinical trials have been conducted to assess whether metformin affects IGF pathways or its binding proteins (20)(21)(22)(23). Unfortunately, this issue remains controversial.…”
Section: Related Biomarkersmentioning
confidence: 99%
“…Studies have been conflicting on whether women with PCOS have higher or similar concentrations of leptin compared with weight-matched controls, but, as expected, leptin concentrations correlate strongly with BMI in both groups (Brzechffa et al 1996, Mantzoros et al 1997b, Kowalska et al 2001, Yildizhan et al 2011. Women with PCOS may actually have higher free concentrations of leptin.…”
Section: Polycystic Ovarian Syndromementioning
confidence: 92%
“…Leptin concentrations do not seem to correlate with concentrations of LH, testosterone, dehydroepiandrosterone sulfate, and estradiol (Brzechffa et al 1996, Mantzoros et al 1997b, Kowalska et al 2001. Pulses of leptin have been found to synchronized with pulses of LH in patients with PCOS, as they are in regularly menstruating women (Sir-Petermann et al 1999).…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…Metformin has a considerable beneficial role in obese PCOS. 17 In a randomized control trial by Batukan et al 4.2% of patients got pregnant at the end of CC cycles and 65.2% of the remaining group got pregnant with metformin plus CC cycles (p=0.0001). 18 Heard et al reported that, metformin alone in patients with PCOS results in a substantial number of pregnancies, with 69% (20/29) of those who ovulated on receiving in less than 6 months.…”
Section: Insulin Sensitizing Agentsmentioning
confidence: 97%